Classroom Management Strategies to Increase the Effectiveness and Efficiency of Physics Learning - Novit, Andariani; Ayuningtiyas, Linda; Kinarsih, Retno Enggar; Bektiarso, Singgih (Universitas Cenderawasih, 2025)
Classroom management is one of the key elements in achieving effective and efficient learning goals, especially in physics subjects. The aim of this article is to analyze the impact of classroom management on student learning outcomes and the factors that influence its effectiveness. This research was conducted using a literature research method which involved analysis of various relevant literature. Analysis shows that good classroom management, including classroom layout, attention to individual student needs, and use of supporting equipment, significantly increases student motivation and achievement of learning outcomes. The biggest challenge in classroom management is the diversity of student characteristics and limited choices. Therefore, teachers need to develop adaptive and creative management skills to create a conducive learning environment. The conclusion of this article confirms that effective classroom management not only supports the physics learning process but also contributes to the overall quality of education.